Effects of replacing hybrid giant napier with sugarcane bagasse and fermented sugarcane bagasse on growth performance, nutrient digestibility, rumen fermentation characteristics, and rumen microorganisms of Simmental crossbred cattle - Jin, Yadong; Huang, Yanru; Luo, Haocen; Wang, Langzhou; Chen, Binlong; Zhang, Yi; Deng, Kaimei; Zhao, Ningbo; Lai, Anqiang (Frontiers in Microbiology, 2023)
This study investigated the effects of replacing hybrid giant napiers with sugarcane bagasse and fermented sugarcane bagasse on the growth performance, apparent nutrient digestibility, rumen fermentation characteristics, and rumen microorganisms of Simmental crossbred cattle. Twenty-one Simmental crossbred cattle with similar initial body weight (363.42 ± 8.67 kg) were randomly divided into three groups: Group CON (20% hybrid giant napier +45% distillers grains +35% concentrate mixture), Group SB (20% sugarcane bagasse +45% distillers grains +35% concentrate mixture), and Group FSB (20% fermented sugarcane bagasse +45% distillers grains +35% concentrate mixture). The average daily weight gain in the SB group was lower than in the CON group, no significant difference was found between the CON and FSB groups. The feed conversion ratio of the CON and FSB groups was lower compared to the SB group. The apparent digestibility of neutral detergent fiber and acid detergent fiber in the SB group was lower than in the CON group, no significant difference was found between the CON and FSB groups. The levels of NH3-N, microbial protein, acetate, propionate, butyrate, isobutyrate, and total volatile fatty acids were higher in the CON and FSB groups than in the SB group, no significant difference was found between the CON and FSB groups. The relative abundances of Christensenellaceae_R-7_group, Rikenellaceae_RC9_gut_group, Prevotellaceae_UCG-003, Saccharofermentans, and Eubacteriumcoprostanoligenes_group were lower in the CON and FSB groups compared to the SB group. The relative abundance of Succiniclasticum was highest in the FSB group, followed by the CON group and then the SB group. Correlation analysis showed that the relative abundance of Succiniclasticum was positively correlated with propionate and NH3-N content, while the relative abundance of Rikenellaceae_RC9_gut_group was inversely correlated with NH3-N content. Gene function prediction indicated that fermented sugarcane bagasse promoted rumen microbial amino acid metabolism. In conclusion, replacing hybrid giant napiers with 20% sugarcane bagasse negatively affected the growth performance of Simmental crossbred cattle, while the addition of 20% fermented sugarcane bagasse had no adverse effects on growth performance and rumen fermentation characteristics, and did not alter the abundance of the rumen core flora in Simmental crossbred cattle.